Social spending and its effect on economic activity across Europe - Volhejn, Petr; Sokol, Ondřej; Formánek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis investigates the relationship between government social spending and economic performance, measured by GDP per capita, across European countries from 2002 to 2022. Using Eurostat data and first differences panel regression models, the study finds a strong, statistically significant positive relationship, with each euro of per capita social spending associated with a GDP increase of approximately 2.94 €. Before excluding or accounting for outliers (Ireland and Norway), the effect was even higher at 3.42 €. Grounded in Keynesian economic theory, and supported by existing literature, the findings suggest that social spending contributes meaningfully to economic growth in institutionally stable contexts. The study highlights limitations including the use of annual data, the exclusion of dynamic models, and the absence of disaggregated spending categories, offering clear directions for future research.
Vedoucí práce: Ondřej Sokol
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analytics [obor bakal. práce]; bakalářské práce; bachelor's theses